Method for enhancing upconversion avalanche nonlinearity based on metal ion regulation sublattice
By doping non-luminescent metal ions into the crystal matrix to induce sublattice contraction, the concentration quenching effect was resolved, resulting in a significant enhancement of upconversion avalanche nonlinearity and improved nonlinear response.
Patent Information
- Application Number
- CN202511230812.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-30
- Publication Date
- 2026-01-16
AI Technical Summary
In existing technologies, when upconversion avalanche nonlinearity is modulated by increasing the activator concentration, a concentration quenching effect is likely to occur, which limits the optimization of the nonlinear response.
By doping non-luminescent metal ions such as Zn2+ or Fe3+ into the crystal matrix, sublattice contraction is induced, shortening the physical distance between activator ions and enhancing the cross-relaxation process, thereby improving the nonlinear response.
It effectively avoids the concentration quenching problem, significantly enhances the upconversion avalanche nonlinearity, nearly doubles the nonlinear parameter, and is simple and universally applicable.
Smart Images

Figure CN121343600A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of nonlinear optics, nanophotonics and material science, and particularly to a method for enhancing upconversion avalanche nonlinearity based on metal ion regulation sublattice. BACKGROUND
[0002] Upconversion nanoparticles (UCNPs) doped with lanthanide elements are a class of advanced luminescent materials that can efficiently convert low-energy near-infrared (NIR) photons into high-energy ultraviolet or visible light photons. Compared with traditional fluorescent materials, UCNPs have unique advantages such as linear emission spectrum, long luminescence lifetime, excellent optical stability, and high signal-to-noise ratio, which make them have great application potential in the fields of biological imaging, sensing detection, optical anti-counterfeiting, and super-resolution imaging.
[0003] The nonlinearity of the upconversion process is its core feature, that is, the emission intensity (I em ) and the excitation light power (P) follow a power law relationship: I em ∝P n , where the exponent 'n' represents the number of photons required to achieve one emission. This highly nonlinear response is the basis for many frontier applications such as super-resolution imaging. Therefore, effectively regulating and enhancing the avalanche nonlinearity response of the material is the key to improving the performance of UCNPs.
[0004] Currently, the main means to regulate nonlinearity is to change the doping concentration of activators (such as Tm 3+ ). Increasing the concentration can shorten the distance between ions, thereby enhancing the interionic energy transfer, including cross relaxation (CR) processes. Specific CR processes can provide efficient energy population paths for upconversion, thereby significantly affecting the nonlinearity. However, this strategy faces a fundamental technical bottleneck, the concentration quenching effect. When the activator concentration exceeds a certain threshold, harmful energy transfer processes (such as energy migration to surface defects or non-radiative CR channels) will dominate, resulting in a decrease in luminescent efficiency instead of an increase. This phenomenon greatly limits the approach of optimizing the nonlinear response by simply increasing the doping concentration.
[0005] Therefore, there is an urgent need in the art for a new method that can precisely shorten the distance between activator ions without introducing or effectively avoiding the concentration quenching effect, thereby actively and controllably enhancing beneficial cross relaxation processes to achieve effective regulation and enhancement of upconversion nonlinearity. SUMMARY
[0006] The technical problem solved by the present application is to overcome the concentration quenching bottleneck inherent in traditional concentration regulation strategies, and to provide a method for enhancing upconversion avalanche ion nonlinear upconversion by inducing sublattice contraction.
[0007] To solve the above technical problems, the technical solution provided by the present application is a method for enhancing upconversion avalanche nonlinearity based on metal ion regulation of sublattice, comprising the following steps:
[0008] S1: selecting a crystal matrix doped with upconversion avalanche activator ions as the activator ions for realizing upconversion avalanche nonlinearity;
[0009] S2: based on the activator ions obtained in S1, doping the crystal matrix with one or more non-luminescent metal ions to replace the matrix cations in the crystal matrix, and completing sublattice contraction;
[0010] S3: the sublattice contraction in S2 acts on the activator ions, shortening the average physical distance of the activator ion pairs in the system, and shortening the ion spacing to enhance the specific cross-relaxation process beneficial to upconversion avalanche nonlinearity;
[0011] S4: using continuous wave excitation to complete the enhancement of upconversion avalanche nonlinearity in the crystal matrix system obtained in S3.
[0012] Preferably, the crystal matrix in S1 is NaYF4, and the upconversion avalanche activator ions include any one of Tm 3+ , Yb 3+ / Pr 3+ , Ho 3+ , Nd 3+ .
[0013] Preferably, the non-luminescent metal ions in S2 include:
[0014] The ionic radius is smaller than that of the matrix cation it replaces;
[0015] Optically inert and does not participate in the upconversion luminescence process.
[0016] Preferably, the non-luminescent metal ions in S2 are a combination of one or more of Zn 2+ , Fe 3+ , and the matrix cation is Y 3+ .
[0017] Preferably, in S2:
[0018] When the non-luminescent metal ions are Zn 2+At that time, its molar fraction of doping in the crystal matrix was 10%;
[0019] When the non-luminescent metal ion is Fe 3+ At that time, its molar fraction of doping in the crystal matrix was 10%.
[0020] Preferably, in S1, the upconversion avalanche activator ion is Tm. 3+ At that time, its molar fraction of doping in the crystal matrix was 8%.
[0021] Preferably, the specific cross-relaxation process in S3 includes being in the state of... 3 Tm at H4 level 3+ Ions and their neighbors 3 Tm of the ground state energy level of H6 3+ Ions undergo cross-relaxation;
[0022] This process can be represented by the following energy level transition path: 3 H4+ 3 H6→ 3 F4+ 3 F4.
[0023] The present invention also discloses a device for detecting the nonlinear upconversion enhancement effect of the above method, comprising an excitation light generation module, a power adjustment and testing module, a sample photoelectric detection module, and an upconversion nanoparticle sample.
[0024] Among them, the excitation light generation module generates a purely linearly polarized near-infrared laser beam;
[0025] The power adjustment and testing module can change the excitation light power by adjusting the half-wave plate and polarizing beam splitter, and split part of the excitation light by the beam splitter for real-time power monitoring.
[0026] The sample photoelectric detection module detects the upconversion fluorescence signal of the sample, and its nonlinear response is determined by analyzing the dependence of fluorescence intensity on excitation light power.
[0027] The advantages of this invention compared to the prior art are:
[0028] Overcoming the concentration quenching limitation: This invention shortens the ion spacing by physically compressing the crystal lattice rather than simply increasing the chemical concentration, effectively avoiding the concentration quenching problem caused by high concentration doping.
[0029] Significantly enhances nonlinearity: Experiments show that this method can improve Tm 3+ The nonlinear parameters of doped NaYF4 nanoparticles are significantly improved (e.g., Zn). 2+ The doping increased the value from 36 to 59, Fe 3+ With doping, the increase can reach as high as 71%, with the maximum increase nearly doubling.
[0030] The method has universality: the lattice engineering strategy has good universality, and is expected to be popularized to other lanthanide ion doped systems (such as Yb 3+ / Pr 3+ , Ho 3+ , Nd 3+ , etc.), for regulating different optical nonlinearities.
[0031] The process is simple, and the method of the present application only needs to add an additional metal salt precursor in the traditional synthesis process, without complex core-shell structure construction or surface modification, and is highly compatible with the existing synthesis process. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 It is a schematic diagram of the principle of the present application for enhancing nonlinear upconversion by inducing sublattice contraction.
[0033] Figure 2 It is a simplified energy level diagram of Tm 3+ ion, showing the cross-relaxation enhancement process.
[0034] Figure 3 It is a detection device for detecting the nonlinear upconversion avalanche nanoparticles.
[0035] Figure 4 It is a double logarithmic relationship diagram of the upconversion emission intensity and excitation power of the nanoparticles prepared in Example 1 and Example 2.
[0036] Figure 5 It is a transmission electron microscope (TEM) diagram of NaYF4:8% Tm nanoparticles prepared in Example 1.
[0037] Figure 6 It is a transmission electron microscope (TEM) diagram of NaYF4:8% Tm, 10% Zn nanoparticles prepared in Example 2.
[0038] Figure 7 It is a transmission electron microscope (TEM) diagram of NaYF4:8% Tm, 10% Fe nanoparticles prepared in Example 2. DETAILED DESCRIPTION
[0039] The present application will be further described in detail below with reference to the accompanying drawings.
[0040] The present application can physically compress the entire lattice by introducing smaller non-luminescent metal ions into the matrix lattice, thereby effectively shortening the physical distance between the activator ions while maintaining the same chemical concentration of the activator. This shortening of the distance greatly enhances the specific cross-relaxation process that is beneficial to nonlinearities, ultimately achieving a significant improvement in nonlinear response.
[0041] It comprises:
[0042] S1: Select a suitable crystal matrix, such as NaYF4 with low phonon energy, to maximize luminescence efficiency. Doping this matrix with Tm, an upconversion avalanche nonlinearity... 3+ ion.
[0043] S2: In the above system, one or more optically inert matrix cations with significantly smaller ionic radii than the one they replace (such as Y) are co-doped. 3+ Metal ions, such as Zn 2+ or Fe 3+ The incorporation of these small-sized ions will replace the original Y atoms in the crystal lattice. 3+ The ions cause a systematic decrease in the cell parameters, that is, sublattice contraction is achieved.
[0044] S3: The overall contraction of the sublattice makes all ions (including Tm)... 3+ -Tm 3+ The average physical distance between ion pairs decreases accordingly. This is because the cross-relaxation rate has an exponentially sensitive dependence on the interionic spacing (R) (typically 1 / R). s (s≥6), this slight reduction in distance greatly amplifies the efficiency of a specific cross-relaxation process. By enhancing the beneficial cross-relaxation channel, key intermediate levels are efficiently populated for subsequent upconversion steps, resulting in a significant enhancement of the nonlinear response on a macroscopic scale.
[0045] It should be noted that the term "sublattice shrinkage" in this invention refers to the slight reduction in lattice parameters caused by impurity ion doping. The Zn selected in this invention... 2+ and Fe 3+ The ionic radii of the ions are all significantly smaller than those of Y. 3+ The incorporation of ions into the NaYF4 lattice leads to a decrease in the lattice constant. This lattice contraction directly affects Tm. 3+ -Tm 3+ The shortening of the spacing creates conditions for frequent cross relaxation.
[0046] It should be noted that Tm 3+ Upconversion luminescence of ions, under 1064 nm continuous-wave excitation, can trigger photon avalanche through a positive feedback loop of ground-state absorption (GSA) + cross-relaxation + excited-state absorption (ESA). For example... Figure 2 As shown, at 1064nm, a small amount of Tm is first absorbed by the ground state. 3+ from 3 H6 fill to 3 F4 energy storage level; subsequently, under the same 1064nm pump, 3 F4→ 3 F 2,3the relative stronger excited state absorption of H4. The Tm 3 Tm of H4 3+ cross relaxation with the neighboring ground state Tm 3+ cross relaxation 3 H4+ 3 H6→ 3 F4+ 3 F4, on one hand, drops itself to 3 F4, on the other hand, pushes the neighboring Tm 3+ ion to 3 F4, thus rapidly accumulating 3 F4 population. 3 The persistent enrichment of F4 significantly improves the ESA probability of F4 at 1064 nm, forming more 3 F4→stronger ESA→more 3 H4→stronger CR→more 3 F4→positive feedback chain. When the pump intensity exceeds the threshold, this feedback is rapidly amplified, and the system appears photon avalanche, with the upconversion luminescence intensity increasing sharply with power and the effective multi-photon order significantly improved. Zn 3 / Fe 2+ induced sub-lattice contraction reduces the Tm 3+ -Tm 3+ spacing, further enhancing the cross relaxation efficiency, and synergistically promoting the avalanche process and high-order nonlinear upconversion from the mechanism.
[0047] It should be noted that the above-mentioned Zn 3+ doping mole fraction of 10% and Fe 2+ doping of 10% are preferred embodiments in the present application, but are not limited thereto. Zn 3+ and Fe 2+ doping amounts can be adjusted as needed, as long as they can induce significant lattice contraction effect and upconversion enhancement. In the embodiments of the present application, the doping mole fraction of Tm 3+ in NaYF4 is 8%, and at this concentration, the Tm 3+ ions have a moderate interaction probability, ensuring a certain upconversion avalanche nonlinearity without causing complete concentration quenching.
[0048] Embodiment 1
[0049] This embodiment provides a comparative experiment to verify the enhancement effect of Zn 3+ doping induced sub-lattice contraction on the upconversion luminescence performance of Tm 2+ Two kinds of nanocrystal samples were prepared: one was a control sample NaYF4:Tm (Tm 3+ doping mole fraction of 20%, and the other was a sample doped with Zn 3+The first type of sample has a doping concentration of 8 mol%. The second type is a NaYF4:Tm,Zn co-doped sample (Tm) prepared by the method provided in this invention. 3+ 8 mol% Zn 2+ (Doped at 10 mol%). Both samples were synthesized by high-temperature co-precipitation method; see Example 3 for specific synthesis steps.
[0050] In the upconversion luminescence performance test, a 1064 nm continuous-wave semiconductor laser was used as the excitation source. Cyclohexane solutions of the two samples were spin-coated onto a glass slide, which was then inverted onto a 1.45 nm objective lens. Figure 3 As shown, the laser, focused by the objective lens, perpendicularly illuminates the glass slide, and the emission spectral signal is collected using a spectrometer. To quantitatively compare the nonlinear order of the upconversion process, this embodiment uses the method of changing the excitation light power density to measure the change in luminescence intensity. While adjusting the excitation light power within a certain range, the relationship between the intensity of the main emission peaks of the two samples and the pump power is recorded. The emission intensity I is plotted against the logarithm of the excitation power P, and linear fitting is performed on the two curves to obtain the power dependence slopes of the control sample and the Zn-doped sample. Figure 4 As shown in the power dependence curves, the slope of the fit for the control sample is approximately 36, indicating that approximately 36 photons are effectively involved in its upconversion process; while Zn 2+ The slope of the doped sample increased to approximately 59, indicating that Zn 2+ The effective number of photons involved in the upconversion process increases significantly after doping. This means that in Zn 2+ Under the induced sublattice contraction, Tm 3+ The cross-relaxation between ions is more pronounced, and higher-order nonlinear upconversions occur compared to traditional systems. This result fully validates the effectiveness of the method proposed in this invention: enhancing Tm through structural modulation. 3+ Cross-relaxation between ions can improve the upconversion luminescence order.
[0051] Example 2
[0052] This embodiment further verifies Fe 3+ Doping with Tm 3+ The effect of upconversion luminescence properties was investigated. A NaYF4:8%Tm control sample and a NaYF4:8%Tm,10%Fe co-doped sample (Fe...) were prepared. 3+ The doping concentration was 10 mol%, and the synthesis method is the same as in Example 3.
[0053] Using the same experimental setup and method as in Example 1, Fe 3+ The upconversion luminescence properties of the doped sample were tested. For example... Figure 4 As shown, by comparing the growth trend of emission intensity in different power ranges under continuous excitation by a 1064nm laser, it can be found that Fe-doped...3+ The sample's power dependence curve slope in the high power region is greatly improved, reaching 71, much higher than the slope value of the undoped sample 36, which is 36. The Fe 3+ doping leads to lattice compression, which improves the nonlinear performance.
[0054] Example 3
[0055] This example illustrates the specific preparation method of the above-mentioned upconversion nanomaterials, including NaYF4:8%Tm matrix and doping
[0056] Zn 2+ and Fe 3+ samples. The method used is high-temperature thermal decomposition co-precipitation, using oleic acid (OA) and 1-octadecene (ODE) as solvent and ligand, NH4F and NaOH as fluorine source and sodium source, to synthesize monodisperse hexagonal phase nanocrystals at high temperature. The preparation processes of the three samples are described below:
[0057] (1) Preparation of NaYF4:8%Tm nanocrystals: At room temperature (23-25°C), 5 mL of 0.2M Ln(CH3COO)3 solution (Ln=Y / Tm) was added to a 100 mL round-bottom flask, followed by the addition of 7.5 mL of oleic acid and 17.5 mL of 1-octadecene. The solution was heated to 120°C for 10 minutes to remove water, and then reacted at 150°C for 40 minutes to form a precursor. After the solution cooled to 40°C, it was kept at this temperature for at least 2 hours. Then, methanol was removed under vacuum at 110°C for 30 minutes. After the methanol evaporated, the temperature was raised to 300°C under argon atmosphere and kept at this temperature for 1.5 hours. Then the same operation as before was performed, and the temperature was lowered to room temperature. 10 mL of anhydrous ethanol was added, centrifuged, the supernatant was discarded, and the product was collected. It was washed with a mixture of ethanol and cyclohexane, and finally dissolved in cyclohexane to obtain NaYF4:8%Tm nanoparticles.
[0058] (2) Preparation of NaYF4:8%Tm,10%Zn nanocrystals: This step prepares co-doped Zn 2+ Tm 3+ upconversion nanocrystals. The basic process steps are the same as (1), except that the initial addition of rare earth acetate solution contains an appropriate amount of Zn(CH3COO)
[0059] 2, to achieve partial substitution of Zn 2+ for Y 3+ . Specifically, a 5 mL 0.2M acetate mixed solution was prepared, containing Y 3 + , Tm 3+ and Zn 2+Three metal ions, i.e. in (1) 10% Zn(CH3COO)2was added. After the solution was added into the flask, 7.5 mL OA and 17.5 mL ODE were added in sequence, and the reaction was carried out according to the same temperature program as in (1). It should be noted that due to the introduction of Zn 2+ , the process of rare earth-oleic acid complex formation and the kinetics of crystal nucleus growth might be slightly changed, but the single-phase NaYF4:Tm,Zn nanocrystals were still successfully prepared under the same conditions in this example. After the reaction was completed and cooled, the same centrifugation and washing steps as in (1) were used, and finally the product was dispersed in cyclohexane for use.
[0060] (3) Preparation of NaYF4:8% Tm, 10% Fe nanocrystals: This step prepared Fe 3+ co-doped Tm 3+ upconversion nanocrystals. The basic process steps were the same as in (2), only 10% Zn(CH3COO)2was replaced by 10% Fe(CH3COO)3.
[0061] Through the above steps, a series of undoped and doped with different ions NaYF4:Tm-based upconversion luminescence nanocrystals were successfully prepared. Transmission electron microscopy (TEM) characterization showed that the nanocrystals had uniform particle size (average particle size about 20 nm), and the morphology was spherical nanoparticle, as shown in Figures 5-7 It can be seen that doping Zn 2+ or Fe 3+ did not significantly change the morphology of the nanocrystals, which indicated that a small amount of impurity ions were uniformly solid-solved into the NaYF4 crystal lattice, and did not form obvious second phases or serious lattice defects.
[0062] The above describes the present application and its embodiments, which is not restrictive, and the drawings shown are only one of the embodiments of the present application, and the actual structure is not limited thereto. In summary, if a person skilled in the art is inspired by it, without departing from the spirit of the present application, without creative design, similar structure and embodiments to the technical solution should belong to the protection scope of the present application.
Claims
1. A method of regulating sublattice enhanced upconversion avalanche nonlinearity based on metal ions, characterized by: The method comprises the following steps: S1: selecting a crystal matrix doped with up-conversion avalanche activator ions as an activating ion for realizing up-conversion avalanche nonlinearity; S2: based on the activating ion obtained in S1, doping the crystal matrix with one or more non-luminescent metal ions to substitute the matrix cations in the crystal matrix, and completing sublattice shrinkage; S3: the sublattice shrinkage in S2 acts on the activator ions, so that the average physical distance of the activator ion pairs in the system is shortened, and the ion spacing is shortened to improve the specific cross-relaxation process beneficial to up-conversion avalanche nonlinearity; S4: using continuous wave excitation to complete the enhancement of up-conversion avalanche nonlinearity of the crystal matrix system obtained in S3.
2. The method of claim 1, wherein the metal ion is selected from the group consisting of Fe3+, Cr3+, Co3+, Ni2+, Cu2+, and Mn2+. The S1 crystal matrix is NaYF4, and the upconversion avalanche activator ions include any one of Tm 3+ , Yb 3+ / Pr 3+ , Ho 3 + , Nd 3+ .
3. The method of claim 1, wherein the metal ions are selected from the group consisting of Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Ag+, and Pb2+. The non-luminescent metal ions in S2 comprise: The ionic radius is smaller than that of the matrix cation to be substituted; Optically inert and does not participate in the up-conversion luminescence process.
4. The method of claim 3, wherein the metal ions are selected from the group consisting of Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Ag+, and Pb2+. The non-luminescent metal ion in S2 is Zn 2+ , Fe 3+ in combination, and the matrix cation is Y 3+ .
5. The method of claim 4, wherein the metal ions are selected from the group consisting of Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Ag+, and Pb2+. In S2: When the non-luminescent metal ion is Zn 2+ at a doping mole fraction of 10% in the crystal matrix; When the non-luminescent metal ion is Fe 3+ at a doping mole fraction of 10% in the crystal matrix.
6. The method of claim 2, wherein the metal ions are selected from the group consisting of Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Ag+, and Pb2+. The S1 when the upconversion avalanche activator ion is Tm 3+ at a doping mole fraction of 8% in the crystal host.
7. The method of claim 6, wherein the metal ions are selected from the group consisting of Fe3+, Cr3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, Hg2+, Ag+, and Pb2+. The specific cross-relaxation process in S3 involves Tm ions in 3 H4 energy level 3+ ions and adjacent Tm ions in 3 H6 ground state energy level 3+ ions undergo cross-relaxation; The process can be represented by the following energy level transition path: 3 H4+ 3 H6→ 3 F4+ 3 F4.
8. A device for detecting the nonlinear upconversion enhancement effect of the method according to any one of claims 1 to 7, characterized in that: It comprises an excitation light generating module, a power adjustment and testing module, a sample photoelectric detection module and an up-conversion nanoparticle sample; The excitation light generating module generates a pure linearly polarized near-infrared laser beam; The power adjustment and testing module can change the excitation light power by adjusting the half-wave plate and the polarization beam splitter prism, and can split part of the excitation light through the beam splitter for real-time power monitoring; The sample photoelectric detection module detects the up-conversion fluorescence signal of the sample, and determines the nonlinear response by analyzing the dependence of the fluorescence intensity on the excitation light power.
